Investigation of local expression of NLRP3 inflammasome complex genes in modeling retinal degeneration in vivo - N. V. Neroeva; O. A. Svitich; V. V. Neroev; A. R. Kinkulkina; N. V. Balatskaya; E. S. Sorozhkina (Медицинская иммунология, 2023)
Neurodegenerative ophthalmopathology is one of the main causes of irreversible blindness and disability in the world. In the pathogenesis of diseases of this group, more and more attention has recently been paid to the role of local inflammation caused by the activation of innate immunity and the mechanisms of its genetic regulation. In recent years, works have appeared in the field of experimental ophthalmology that have demonstrated the possibility of NLRP1, NLRP3 inflammasome complexes assembling when exposed to hyperglycemia, oxygen deprivation of retinal cells, as well as modeling compressive stress similar to that in glaucoma [15]. However, the mechanism of inflammasome involvement in the development of neurodegenerative eye diseases remains unclear. The aim of the study was to investigate the local expression of genes encoding proteins of the NLRP3 inflammasome complex (NLRP3, CASP-1) in an experimental model of retinal degeneration in rabbits. The studies were performed on samples of tissue complex (TC) of the retina/retinal pigment epithelium (RPE) (retina/RPE TC), isolated from the eyes of 14 New Zealand albino rabbits, in which degenerative retinal lesion was modeled by a single subretinal injection of 0.01 mL of 0.9% sodium chloride solution, and 7 healthy rabbits without eye damage. The formation of retinal degeneration was judged on the basis of changes in morphofunctional parameters obtained during specialized ophthalmological research methods (optical coherence tomography, fundus autofluorescence, electroretinography) at follow-up periods of 1, 3 and 6 months. The level of expression of NLRP3 and CASP-1 genes in the retina/RPE TC was evaluated by reverse transcription polymerase chain reaction (RT-PCR). According to the results of the study, a statistically significant increase in NLRP3 gene expression (p < 0.001) was noted in the retina/RPE TC of experimental animals, which may indicate the involvement of NLRP-3 inflammasome components in the development of neurodegenerative retinal lesions. At the same time, the expression of the gene encoding CASP-1 was detected only in the retina/RPE TC of experimental eyes and is probably due to local inflammatory mechanisms in the retinal tissue.The high level of NLRP3, CASP-1 mRNA, detected in all retina/RPE TC samples of experimental eyes at late stages of the experiment (3 and 6 months), allows us to assume the formation of mechanisms (for example, activated glial phenotype) that support inflammation in retinal tissue. This should be taken into account in actively developing transplantation methods for the treatment of retinal degeneration.